THE ANCILLARY PRODUCTS OF RUBBER (Hevea brasiliensis Muell. Arg.): POTENTIAL RESOURCES TO ENHANCE SUSTAINABILITY - J Junaidi (Agricultural Socio-Economics Journal, 2022)
Indonesia is one of the major natural rubber-producing countries. The low rubber prices severely affect rubber agribusiness as farmers and rubber companies depend on latex as the only source of income. This condition leads to an unprecedented challenge to rubber agribusiness sustainability. This systematic review aims to encourage the use of part of rubber plants as a source of revenue for rubber plantations to maintain their sustainability. Non-latex parts of the rubber plant can be utilized, including latex serum and skim waste, parts of rubber seeds, and rubberwood. The strength of the ancillary product of Hevea brasiliensis is that the raw materials are abundant, yet the weakness is that the rubber companies have no experience exploiting them. The opportunity for utilizing is widely open, as many methods have been researched; however, the main thread is how to compete with the existing products. Therefore, careful market research and feasibility studies are recommended.